2018
DOI: 10.1029/2018jc013755
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclone Boundary Layer Rolls in Synthetic Aperture Radar Imagery

Abstract: Marine atmospheric boundary layer (MABL) roll plays an important role in the turbulent exchange of momentum, sensible heat, and moisture throughout MABL of tropical cyclone (TC). Hence, rolls are believed to be closely related to TC's development, intensification, and decay processes. Spaceborne synthetic aperture radar (SAR) provides a unique capability to image the sea surface imprints of quasi‐linear streaks induced by the MABL rolls within a TC. In this study, sixteen SAR images, including three images acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Note that multiple peaks are visible, principally associated with irregularities in the main linear features throughout the image scene. Still a dominant azimuthal peak direction is apparent and similar FFT methodologies have been used to extract the dominant orientation of MABL rolls (Gerling, 1986;Mourad and Walter, 1996;Li et al, 2013;Huang et al, 2018). depth, or contrast, is obtained after normalization by their average (σ 0…”
Section: Extraction Of Roll-induced Backscatter Modulation Amplitude and Directionmentioning
confidence: 99%
“…Note that multiple peaks are visible, principally associated with irregularities in the main linear features throughout the image scene. Still a dominant azimuthal peak direction is apparent and similar FFT methodologies have been used to extract the dominant orientation of MABL rolls (Gerling, 1986;Mourad and Walter, 1996;Li et al, 2013;Huang et al, 2018). depth, or contrast, is obtained after normalization by their average (σ 0…”
Section: Extraction Of Roll-induced Backscatter Modulation Amplitude and Directionmentioning
confidence: 99%
“…Of note, Huang et al 13 found that km-scale and sub-km-scale rolls coexist in the TCBL by analyzing many Synthetic Aperture Radar (SAR) images. Gall et al 14 documented large scale (~ 10 km) rolls in landfalling hurricanes.…”
Section: Introductionmentioning
confidence: 99%
“…For high winds, MABL rolls are prevalent in the TC boundary layer. The surface imprints of kilometer-scale roll vortices are clearly visible in the SAR images of hurricanes [20], [21]. In particular, 3-6-km wavelength roll vortices have been associated with secondary circulations between the main TC rain bands [1].…”
Section: Introductionmentioning
confidence: 99%